Cobalt nanoparticles supported on alumina nanofibers (Co/Al2O3): Cost effective catalytic system for the hydrolysis of methylamine borane. (1st November 2019) - Baguc, Ismail Burak; Yurderi, Mehmet; Bulut, Ahmet; Celebi, Metin; Kanberoglu, Gulsah Saydan; Zahmakiran, Mehmet; Kaya, Murat; Aydemir, Murat; Durap, Feyyaz; Baysal, Akın
Abstract: Amongst different amine-borane derivatives, methylamine-borane (CH3 NH2 BH3 ) seems to be one of the capable aspirants in the storing of hydrogen attributable to its high hydrogen capacity, stability and aptitude to generate hydrogen through its catalytic hydrolysis reaction under ambient conditions. In this research paper, we report that cobalt nanoparticles supported on alumina nanofibers (Co/Al2 O3 ) are acting as active nanocatalyst for catalytic hydrolysis of methylamine-borane. Co/Al2 O3 nanocatalyst was fabricated by double-solvent method followed with wet-chemical reduction, and was characterized by utilizing various spectroscopic methods and imaging techniques. The results gathered from these analyses showed that the formation Al2 O3 nanofibers supported cobalt(0) nanoparticles with a mean diameter of 3.9 ± 1.2 nm. The catalytic feat of these cobalt nanoparticles was scrutinized in the catalytic hydrolysis of methylamine-borane by considering their activity and durability performances. They achieve releasing of 3.0 equivalent of H2 via methylamine-borane hydrolysis at room temperature ( initial TOF = 297 mol H2 /mol metal × h). Along with activity the catalytic durability of Co/Al2 O3 was also studied by carrying out recyclability tests and it was found that these supported cobalt nanoparticles have good durability during the course of the catalytic recycles so that Co/Al2 O3 preserves almost its innate activity at 5th catalytic recycle. The studies presented here also contains kinetic investigation of Co/Al2 O3 catalyzed methylamine borane hydrolysis depending on the temperature, cobalt and methylamine borane concentrations, which were used to define rate expression and the activation energy of the catalytic reaction. Graphical abstract: Image 1 Highlights: Co/Al2 O3 nanocatalyst was synthesized and characterized by using advanced techniques, Co/Al2 O3 was employed in the hydrolytic dehydrogenation of methylamine-borane (CH3 NH2 BH3 ) Co/Al2 O3 provides high catalytic activity (TOF = 297 mol H2 /mol Co × h) in this important reaction.